2022
DOI: 10.1107/s1600577522008165
|View full text |Cite
|
Sign up to set email alerts
|

Chemical characterization of inks in skin reactions to tattoo

Abstract: Skin reactions are well described complications of tattooing, usually provoked by red inks. Chemical characterizations of these inks are usually based on limited subjects and techniques. This study aimed to determine the organic and inorganic composition of inks using X-ray fluorescence spectroscopy (XRF), X-ray absorption spectroscopy (XANES) and Raman spectroscopy, in a cohort of patients with cutaneous hypersensitivity reactions to tattoo. A retrospective multicenter study was performed, including 15 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…However, targeted 532 nm lasers designed for green light can effectively address these pigments [26]. Red tattoos, typically composed of organic pigments [27], exhibit good response to 532 nm lasers that coincide with their absorption peak [4]. Conversely, yellow tattoos with broad absorption spectra pose greater difficulty in achieving complete clearance [28].…”
Section: Discussionmentioning
confidence: 99%
“…However, targeted 532 nm lasers designed for green light can effectively address these pigments [26]. Red tattoos, typically composed of organic pigments [27], exhibit good response to 532 nm lasers that coincide with their absorption peak [4]. Conversely, yellow tattoos with broad absorption spectra pose greater difficulty in achieving complete clearance [28].…”
Section: Discussionmentioning
confidence: 99%
“…Some people suffer hypersensitivity reactions of the skin from the use of tattoo inks and potential insights as to the causes have been investigated using XRF, XANES and Raman spectroscopy. 83 Analysis of skin biopsies of affected patients showed the presence of a suite of metals, Cr, Cu Fe, Mn, Ni, Ti and Zn, which could have tattoo ink origins and also the pigment carbon black. XANES analysis identified that the Fe species were present as oxyhydroxides, and that Fe III+ was present in an octahedral environment, suggesting that the Fe present was not of endogenous origin.…”
Section: Elemental Speciation Analysismentioning
confidence: 99%
“…These hazardous substances are thought to be particularly dangerous when tattoos are extensive. Given these concerns, there is a renewed interest in further studying the possible toxic effects25 27 28 34–36 or malignancies30–33 37 38 associated with tattoos.…”
Section: Introductionmentioning
confidence: 99%
“…The WHO has now established regulatory measures for tattoo ink components23 25 in addition to other existing international recommendations,42–44 but quality control and monitoring remain difficult and unreliable. This situation—coupled with the increasing number of individuals with large tattoos and, consequently, a growing number of CNBs in tattooed areas—increases the likelihood of diagnosed pathological cases in the near future 5 23 34 40 45…”
Section: Introductionmentioning
confidence: 99%